Kajian Keruangan Pola Sebaran Strategi Pembelajaran Dalam Kegiatan PPL II (Studi Kasus: Mahasiswa S1 Pendidikan Geografi Universitas Nusa Cendana di Kota Kupang) - Arfita Rahmawati; Radhi Ariawan (UM Purwokerto Press, 2021)
Practical Field Experience (PPL) II is a compulsory subject, especially for prospective teachers. Practical Field Experience (PPL) II is a time for teaching students to practice learning knowledge in school partners. The Covid-19 pandemic occurred changed the PPL II system from offline to online. The online PPL system provides new experiences for students, including in determining the learning strategies to use. The purpose of this study to determine the distribution patterns of learning strategies in PPL II so can saw the learning strategies that are most popular among students and their spatial patterns. This study used questionnaire data that was distributed to 88 students then carried out NNA analysis to determine the spatial pattern and linear regression analysis. Based on the research results, it is known that the popular learning strategy used by students when PPL II is a cooperative learning strategy with a value of 44.318%. The spatial pattern based on the distribution of learning strategies used for cooperative learning, contextual and Problem Based Learning is clustered or clustered. As for the random patterned inquiry learning strategy. There is an influence from the learning strategies used by students on the level of satisfaction of school partners.